2020
DOI: 10.1177/0921374020909516
|View full text |Cite
|
Sign up to set email alerts
|

Divided we tweet: The social media poetics of public online shaming

Abstract: This article explores the divisive nature of social media public culture in which impromptu communities of strangers affirm or antagonize one another in non-face-to-face interactions through memes, hashtags, and other posts. Drawing upon the work of Michael Herzfeld, specifically his notion of cultural intimacy and social poetics, this article analyzes contemporary politicized social media to demonstrate what I call social media poetics, briefly, public online shaming through which antagonists criticize one an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…Interestingly, the privacy concerns of shamed children are not necessarily about the intrusion, seclusion or disclosure of embarrassing information, but rather, about the disruption in their ability to continue to participate in online spaces free from attacks (Dilmac, 2014). Recently, Shenton (2020) analyzed contemporary social media and suggested that public online shaming is also an antagonistic “poetic” practice through which users forge their identities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interestingly, the privacy concerns of shamed children are not necessarily about the intrusion, seclusion or disclosure of embarrassing information, but rather, about the disruption in their ability to continue to participate in online spaces free from attacks (Dilmac, 2014). Recently, Shenton (2020) analyzed contemporary social media and suggested that public online shaming is also an antagonistic “poetic” practice through which users forge their identities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Como sujetos activos productores de discursos, se someten a la polarización que refuerza el antagonismo de la práctica y la oposición de la lucha. En este sentido, se pueden distinguir posters partidarios, defensores, liberales y conservadores (Shenton, 2020), según la práctica. Por su parte, los lurkers son mayorías silenciosas que interactúan, leen la información publicada por las organizaciones de protesta, pero no publican o emiten enunciados de apoyo en sus interacciones digitales (Sun, Rau y Ma, 2014).…”
Section: Actantes De La Protesta Online Y Offlineunclassified
“…Nuestro punto de partida asumirá la perspectiva del rito no para reconocer sus características étnicas como protesta social, sino, en un camino inverso, para aproximarnos a la protesta como rito. La literatura sobre la protesta digital (Panagiotopoulos, 2012;Vaccari y Valeriani, 2015;Shenton, 2020) y la protesta en espacios públicos (Fillieule y Tartakowsky, 2015;Panfichi y Coronel, 2014;Osisanwo e Iyoha, 2020;Domínguez y Malca, 2019) es abundante y de gran actualidad. No obstante, presenta un vacío de investigación respecto a las consideraciones de la protesta como práctica ritual.…”
Section: Introductionunclassified
“…Social networks have an online disinhibition effect, which makes it easier for a person behind a keyboard to write things that they would probably not say to others in person. Conventional social network practices such as the use of memes, hashtags and shaming exacerbate a sense of difference and otherness (Shenton, 2020). As a result, social network discourse is more intense and divisive (Laor, 2022; Shenton, 2020; Norlock, 2017), and people's opinions on various issues, including government trust, become more polarized.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional social network practices such as the use of memes, hashtags and shaming exacerbate a sense of difference and otherness (Shenton, 2020). As a result, social network discourse is more intense and divisive (Laor, 2022; Shenton, 2020; Norlock, 2017), and people's opinions on various issues, including government trust, become more polarized. As a result, various conspiracy theories flourish on the Internet during a crisis.…”
Section: Introductionmentioning
confidence: 99%